Remote teaching and learning in the middle and high ELA classroom : instructional strategies and best practices - Ruday, Sean; Cassidy, Jennifer (New York, NY : Routledge, 2022)
"Teaching in remote, distance, and hybrid environments can be overwhelming and confusing, and poses many challenges for novice and veteran teachers alike. This book will guide through the best practices of English language arts instruction, and help you reflect on ways to apply those practices in remote learning and envision future instruction that draws from the most useful aspects of educational innovations. Understanding that remote teaching looks different in each subject, Ruday and Cassidy identify methods specifically designed for middle and high school ELA classrooms. Designed for use in remote, hybrid, and hyflex environments with synchronous or asynchronous learning, this resource gives teachers a toolbox of research-backed recommendations, ideas, examples, and practices for teaching in unpredictable and new environments. Ruday and Cassidy address essential topics, including writing, grammar, and reading instruction; assessment; differentiation; culturally relevant teaching; family engagement and communication; technology; professional self-care; and more. Teachers will come away with ready-to-implement strategies and insights for high-quality instruction that can be adapted to any kind of remote learning environment"--
Keywords: Distance education; English language -- Study and teaching (Middle school); English language -- Study and teaching (High school); Web-based instruction; Blended learning; Technological innovations